Maranaw indigenous games - Bueno, Wilfredo Belvis, Sr (1978)
This is a descriptive study of Maranao indigenous games. Maranaw games were chosen because the Maranaws constitute one of the largest and most advanced Muslim group in Mindanao who have managed to shield their indigenous culture from Western influences. The researcher came up with 40 games, fully described, with English translation for Maranaw term, and individually indexed according to (a) suitability by age or school level, (b) venue or recommended playing area, (c) number of players, and (d) materials needed. This was done primarily for easy reference by physical education teachers and curriculum planners for whom this work was mainly designed.